Impact of Rishikesh-Karanprayag railway line on the agroecosystem of Maletha village of Garhwal Himalaya - Ruchika Sharma; B.S. Bhandari; Sarita Kumari; Arti Falswal (Environment Conservation Journal, 2021)
Uttarakhand is a newly incepted state, geographically and culturally distinct from the plains and is the prime destination of tourists not only from India but also from different parts of the globe. Railways in Uttarakhand will certainly play a crucial role in the development of the state. Ministry of Railways of India has launched and initiated a project to connect the Char dhams of the state which will surely prove a landmark in the developmental feat of the state but development and modernization at the cost of disturbing the ecosystem in general and agricultural ecosystem in particular will create an imbalance in the livelihood of the people who by and large depend on agriculture economy. The present study was carried out in an agriculturally rich medium sized village of Uttarakhand. The survey reveal that climatic and geographical conditions of the village are suitable for the cultivation of large number of vegetables, fruits, cereals, millets, pulses and fodder plants supporting the livelihood of the natives. Land acquisition would have a negative impact on the socio-economic condition of the farmers as well as on the traditional crop diversity of the area as the railway project covers most of the fertile land. Thus, for reducing the havoc in the lives of the villagers government should provide land as an exchange as most of the population is agriculture dependent and at the same time degradation should be viewed with long-term vision